Effects of constant light during perinatal periods on the behavioral and neuronal development of mice with or without dietary lutein - YAJIMA, Masako; MATSUMOTO, Megumi; HARADA, Michiko; HARA, Hiroshi; YAJIMA, Takaji (Biomedical Research, 2013)
Constant light conditions (LL) carry a risk of disrupting the biological clock of developing animals. Our purpose in this study was to investigate what disorders occur in animals receiving an LL stress during the late embryonic and suckling periods as compared with animals housed in dark-light (14 h-10 h) conditions (DL). In addition, we examined ameliorating effects against the disorder by the oral administration of lutein as an antioxidant. LL caused hypertrophy of the spleen and induced a higher expression of serotonin transporter (5HTT) in the corpus striatum and hippocampus in 15-day-old pups. In 9-week-old offspring, LL caused abnormal behavior in the elevated plus-maze test. The expression levels of 5HTT in the brain of the LL group changed to lower than those in DL group. The oral administration of lutein lessened the abnormality in behavior and 5HTT expression in the hippocampus to a certain degree although the expression levels of 5HTT in the corpus striatum were not altered by lutein diet. LL also induced disorders in the maternal brain with lower expression levels of 5HTT and neuregulin 1. These results indicate that LL during the perinatal periods may induce some neuronal abnormalities in both offspring and mothers that may be partially ameliorated by dietary lutein as an antioxidant.